Associations of prenatal urinary melamine, melamine analogues, and aromatic amines with gestational duration and fetal growth in the ECHO Cohort - Giehae Choi; Xiaoshuang Xun; Deborah H. Bennett; John D. Meeker; Rachel Morello-Frosch; Sheela Sathyanarayana; Susan L Schantz; Leonardo Trasande; Deborah Watkins; Edo D. Pellizzari; Wenlong Li; Kurunthachalam Kannan; et al. (Environment International)
Melamine, its analogues, and aromatic amines (AAs) were commonly detected in a previous study of pregnant women in the Environmental influences on Child Health Outcomes (ECHO) Cohort. While these chemicals have identified toxicities, little is known about their influences on fetal development. We measured these chemicals in gestational urine samples in 3 ECHO cohort sites to assess associations with birth outcomes (n = 1,231). We estimated beta coefficients and 95% confidence intervals (CIs) using adjusted linear mixed models with continuous dilution-standardized concentrations (log2 transformed and scaled by interquartile range, IQR) or binary indicators for detection. As secondary analyses, we repeated analyses using categorical outcomes. Forty-one of 45 analytes were detected in at least one sample, with > 95 % detection of melamine, cyanuric acid, ammelide, and aniline. Higher melamine concentration was associated with longer gestational age (β^ per IQR increase of log2-transformed: 0.082 [95 % CI: −0.012, 0.177]; 2nd vs 1st tertile: 0.173 [-0.048, 0.394]; 3rd vs 1st tertile: 0.186 [-0.035, 0.407]). Similarly in secondary analyses using categorical outcomes, an IQR increase in log2(melamine) was associated with 1.22 [0.99, 1.50] higher odds of post-term (>40 & ≤42 weeks) as compared to full-term (≥38 & ≤40 weeks). Several AAs were associated with birthweight and gestational length, with the direction of associations varying by AA. Some stronger associations were observed in females. Our findings suggest melamine and its analogs and AAs may influence gestational length and birthweight.